Prevalence and factors associated with the presence of oral infections in pregnant women in a medium-sized municipality in Brazil - A.P.N. Godoi; G.C.S. Bernardes; L.N. Godoi; L.S. Nogueira; G.M. Rocha; M. Barros-Pinheiro (Brazilian Journal of Medical and Biological Research)
The objective of this study was to estimate the prevalence and factors associated with oral changes, including infections and other oral conditions in pregnant women who underwent prenatal care in public health units in the city of Divinópolis, Minas Gerais. This was a cross-sectional study carried out with baseline data from a cohort of 588 pregnant women (aged 14 to 43 years) from 2019 to 2023. Data were collected through interviews and oral clinical examination, using a structured questionnaire. The event of interest was the presence of oral infection. The absolute and relative frequencies of the variables were calculated. Logistic regression was used to evaluate the association between the explanatory variables and the presence of oral infection, with estimation of odds ratios and 95% confidence intervals. Among the participants, 47.8% had oral infections. In the multivariate analysis, the variables that showed a significant association with oral infection were: lower education, last visit to the dentist more than 6 months ago, lower frequency of flossing, regular intake of alcoholic beverages, and self-report of poor oral health. This study highlighted sociodemographic and behavioral disparities and the importance of prenatal dental care. Insights for adapting interventions were provided, although further studies are needed.